Outcomes of advanced and recurrent cervical cancer treated with cisplatin and generic topotecan: Retrospective analysis in a tertiary care hospital in Thailand - Suprasert P. (2017)
Objective: Retrospective evaluation of the outcome of stage IVB, recurrent or persistent cervical cancer treated with cisplatin and generic topotecan (CT) in a tertiary care hospital in Thailand. Methods: The medical records of patients treated with CT regimen at Chiang Mai University Hospital between January 2005 and December 2007 were reviewed and analyzed. The treatment protocol consisted of IV topotecan 0.75 mg/m 2 on days 1, 2, and 3; combined with cisplatin 50 mg/m 2 IV on day 1 and repeated every 21 days until progression or unacceptable toxicity for a maximum of 6 cycles. The outcomes were evaluated based on the response rate, progression free survival (PFS), and overall survival (OS) by using the World Health Organization criteria. The adverse effects of the treatments were also determined. Results: Twenty-one cervical cancer patients received the CT regimen. The tumor response rate was 28.6%. The median PFS and OS was 4 and 11 months, respectively. With 87 cycles of chemotherapy, the most common grade 3 & 4 hematologic toxicity was neutropenia (57.9%). Conclusion: Advanced and recurrent cervical cancer patients treated with cisplatin and generic topotecan had a favorable outcome with manageable toxicity.